2007
DOI: 10.1074/jbc.m609478200
|View full text |Cite
|
Sign up to set email alerts
|

Association of CD38 with Nonmuscle Myosin Heavy Chain IIA and Lck Is Essential for the Internalization and Activation of CD38

Abstract: Activation of CD38 in lymphokine-activated killer (LAK) cells involves interleukin-8 (IL8)-mediated protein kinase G (PKG) activation and results in an increase in the sustained intracellular Ca2؉ concentration ([Ca 2؉ ] i ), cADP-ribose, and LAK cell migration. However, direct phosphorylation or activation of CD38 by PKG has not been observed in vitro. In this study, we examined the molecular mechanism of PKG-mediated activation of CD38. Nonmuscle myosin heavy chain IIA (MHCIIA) was identified as a CD38-assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 40 publications
2
31
0
Order By: Relevance
“…S5), although the exact mechanism has yet to be elucidated. Therefore, as we previously observed that IL-8-induced cADPR formation requires internalization of CD38 from the plasma membrane (40), but NAADP production is mediated by CD38 expressed in lysosomes via Ca 2ϩ release from the endoplasmic reticulum and cAMP/Epac/PKA/Rap 1 signaling.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…S5), although the exact mechanism has yet to be elucidated. Therefore, as we previously observed that IL-8-induced cADPR formation requires internalization of CD38 from the plasma membrane (40), but NAADP production is mediated by CD38 expressed in lysosomes via Ca 2ϩ release from the endoplasmic reticulum and cAMP/Epac/PKA/Rap 1 signaling.…”
Section: Discussionmentioning
confidence: 66%
“…S6) suggests that 2ϩ levels results in elevation of cGMP levels via guanylyl cyclase (GC), thus activating protein kinase G (PKG) (24). Phosphorylated nonmuscle myosin IIA (MHCIIA) by protein kinase G is recruited in the CD38-Lck complex, inducing the internalization of CD38 and cADPR production (40). The cADPR produced by CD38 in the endocytic vesicles is transported via the promiscuous nucleoside/cADPR transporters, as previously described (35), or by the internalized CD38 itself, as previously proposed (61).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This internalizing event has been observed in many different cellular responses where cADPR production is shifted from the surface to inside the cell (22,23). It has been suggested that the internalization mechanism is mediated by non-muscle myosin heavy chain IIA (MHCIIA), where both CD38 and MHCIIA were found to be associated in activated lymphokine-activated killer cells (24). Phagocytosis is the mechanism of internalization used by phagocytes to internalize and degrade microorganisms, cell debris, and various particles (25).…”
mentioning
confidence: 99%